Survival, mortality and morbidity outcomes after oesophagogastric cancer surgery in New South Wales, 2001–2008. Issue 7 (21st April 2014) - Smith, Ross C; Creighton, Nicola; Lord, Reginald V; Merrett, Neil D; Keogh, Gregory W; Liauw, Winston S; Currow, David C
Abstract: Objectives: To examine the relationship between hospital volume and patient outcomes for New South Wales hospitals performing oesophagectomy and gastrectomy for oesophagogastric cancer. Design, setting and patients: A retrospective, population‐based cohort study of NSW residents diagnosed with a new case of invasive oesophageal or gastric cancer who underwent oesophagectomy or gastrectomy between 2001 and 2008 in NSW hospitals using linked de‐identified data from the NSW Central Cancer Registry, the National Death Index and the NSW Admitted Patient Data Collection. A higher‐volume hospital was defined as one performing > 6 relevant procedures per year. Main outcome measures: Odds ratios for > 21‐day length of stay, 28‐day unplanned readmission, 30‐day mortality and 90‐day mortality, and hazard ratios (HRs) for 5‐year absolute and conditional survival. Results: Oesophagectomy (908 patients) and gastrectomy (1621 patients) were undertaken in 42 and 84 hospitals, respectively, between 2001 and 2008. Median annual hospital volume ranged from 2 to 4 for oesophagectomies and ranged from 2 to 3 for gastrectomies. Controlling for known confounders, no associations between hospital volume and > 21‐day length of stay and 28‐day unplanned readmission were found. Overall 30‐day mortality was 4.1% and 4.4% for oesophagectomy and gastrectomy, respectively. Five‐year absolute survival was significantly better for patients who underwent oesophagectomy in higher‐volume hospitals (adjusted HR for lower‐volume hospitals, 1.28 [95% CI, 1.10–1.49]; P = 0.002) and for those with localised gastric cancer who underwent gastrectomy in higher‐volume hospitals (adjusted HR for lower‐volume hospitals, 1.83 [95% CI, 1.28–2.61]; P = 0.001). Conclusions: These data support initial surgery for oesophagogastric cancer in higher‐volume hospitals.